Determinants of The Intention to Reuse E-Money in Generation Z - Nyoman Dwika Ayu Amrita; Ni Ketut Sukanti; Made Ayu Desy Geriadi (Jurnal Ekonomi dan Bisnis Jagaditha, 2023)
Non-cash money or electronic money (e-money) is a means of payment that has the characteristics of being issued on the basis of the value of money deposited first by the holder to the issuer, the value of money stored electronically in a medium such as a server or chip, used as a means of payment to merchants who are not the issuer of the electronic money and the value of electronic money deposited by the holder and managed by the issuer is not a deposit as referred to in the laws governing banking. This study aims to examine the intention to reuse e-money in generation Z in Denpasar City in terms of the perceived usefulness, perceived ease of use and perceived risk and to find out the influence of perceived usefulness, perceived ease of use and perceived risk on the intention to reuse e-money and to find out which of these three variables has the greatest influence on the intention to reuse e-money. The subjects were e-money users, with a sample of 110 people. The sample was determined using a non-probability sampling method, namely purposive sampling. This study uses quantitative methods with multiple linear regression data analysis techniques with data collection through interviews, documentation and questionnaires. The results of the data analysis showed that simultaneously and partially, the perceived usefulness, the perceived ease of use and the perceived risk influence to the intention of reusing e-money.